The expectations and aspirations of a late-career professional woman. (December 2015) - Atkinson, Carol; Ford, Jackie; Harding, Nancy; Jones, Flora
This article presents a powerful account of one late-career woman's lived experiences. Little is known about women who continue professional careers into their 50s and beyond. Here insights are offered into her aspirations and expectations, as she reflects upon a career fragmented by gendered caring responsibilities and the implications of ageism and sexism together with health and body for her late-career phase. The narrative enhances understanding of the intersection of age and gender in a context where masculine career norms dominate. It also offers a reflection upon the implications of these themes for late-career women and their employing organizations more generally.